2000
DOI: 10.1212/wnl.54.9.1832
|View full text |Cite
|
Sign up to set email alerts
|

Oral zolmitriptan is effective in the acute treatment of cluster headache

Abstract: Oral zolmitriptan is efficacious in episodic cluster headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 30 publications
6
126
1
2
Order By: Relevance
“…In a double-blind crossover study, significantly more patients with ECH reported efficacy of oral zolmitriptan than placebo (46.8% vs. 28.9%) [25]. In CCH however, there was no significant difference.…”
Section: Therapymentioning
confidence: 94%
“…In a double-blind crossover study, significantly more patients with ECH reported efficacy of oral zolmitriptan than placebo (46.8% vs. 28.9%) [25]. In CCH however, there was no significant difference.…”
Section: Therapymentioning
confidence: 94%
“…Most required that participants had previously tolerated treatment with a triptan, and/or had no contraindications, but Ekbom 1991 and Ekbom 1993 recruited only sumatriptan-naïve participants. In four studies participants self-treated their headaches at home (Bahra 2000;Cittadini 2006;Van Vliet 2003), while in the other two medication was administered by a physician or nurse in hospital (Ekbom 1991;Ekbom 1993). We included these hospital-based studies because although the intervention was not self-administered in these cases, subcutaneous sumatriptan can be, and is commonly, self-administered.…”
Section: Assessment Of Reporting Biases-no Formal Tests Were Plannedmentioning
confidence: 99%
“…No study directly compared one drug with another. Oral zolmitriptan 5 mg and 10 mg were tested in one study (Bahra 2000), and intranasal zolmitriptan 5 mg and 10 mg in two studies (Cittadini 2006;). …”
Section: Assessment Of Reporting Biases-no Formal Tests Were Plannedmentioning
confidence: 99%
“…Recently, a double-blind controlled trial compared the efficacy of 5 and 10 mg oral zolmitriptan with placebo for the treatment of acute CH attacks [12]. With headache response defined as a two-point reduction on a five-point pain intensity scale at 30 min, response rates following placebo, 5 and 10 mg of zolmitriptan, were 29%, 40% and 47%, respectively.…”
Section: Zolmitriptanmentioning
confidence: 99%